(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the functional outcome of closed humeral shaft fractures treated with functional brace. Methods: This descriptive study was conducted in Orthopedic Department District Headquarter hospital Teaching Hospital Kohat Development Authority(KDA) Kohat and Khyber Teaching Hospital Peshawar from 23rd February 2018 to 23rd February 2020.All patients with humeral shaft fractures meeting the inclusion criteria were treated with functional brace. Functional assessment was done at 6 months follow up according to Stewart and Hundley criteria and graded as good, fair and poor. Results: The total number of patients in this study were 22. The mean age was 36.23±9.05 years. Males patients were 14 (63.64%) and females were 8 (36.36%). According to Stewart and Hundley criteria, functional outcome in our patients was good in 17(77.27%) patients, fair in 3(13.64%) and poor in 2(9.09%)patients. We achieved union in 20 (90.91%) patients. However, non-union was seen in 2 (9.09%) patients. Conclusion: Closed humeral shaft fractures treated with functional brace had satisfactory union rates and good functional outcome in majority of our patients.